Multiple soliton solutions of second-order Benjamin-Ono equation - Najafi, M (TWMS journal of applied and engineering mathematics, 2012)
We employ the idea of Hirota's bilinear method, to obtain some new exact soliton solutions for high nonlinear form of Multiple soliton solutions of second-order Benjamin-Ono equation. Multiple singular soliton solutions were obtained by this method. Moreover, multiple singular soliton solutions were also derived. Keywords: Hirota bilinear method, Benjamin-Ono equation, Multiple soliton solutions, Multiple singular soliton solutions. AMS Subject Classification: 35C07, 35C08, 35A25